(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
In response to the environmental concerns posed by low-density polyethylene (LDPE) pollution, this study explores the potential of natural fibers—specifically banana and luffa fibers—as reinforcements in recycled LDPE composites. Composites were fabricated by blending post-consumer rLDPE with banana and luffa fibers at weight ratios of 10%, 20%, and 30%. Mechanical properties: tensile strength, flexural strength, elongation at break, and impact resistance tests were evaluated. Results showed that banana fiber composites exhibited an increase in tensile strength from 12.4 MPa to 13.99 MPa with increasing fiber content (10%–30%), The flexural strength decreases from 125.9 MPa at, 105MPa, and 92.74 MPa at 30% of fibre loading, while elongation at break, the elongation increases from 14.51% at 10% to 35.31% at 30%. However, both flexural strength and impact resistance decreased with increased fiber loading, likely due to poor fiber-matrix interfacial bonding. Optimal performance for banana-reinforced composites was observed at 30% fiber content for tensile strength, and at 10% for flexural strength. In contrast, luffa fiber composites showed a decrease in tensile strength from 11.84 MPa to 10.07 MPa as fiber content increased, attributed to weak interfacial adhesion. Flexural strength increased from 10MPa to 57.78MPa fiber loading. Elongation decreased from 44.62%-25%, but slightly increased 25%-28% as fibre loading increases due to poor fiber-matrix interfacial bonding. Overall, banana fiber demonstrated more consistent and favorable mechanical performance than luffa, particularly in tensile properties, highlighting its potential as a sustainable reinforcement material in rLDPE composites to mitigate plastic waste and reduce environmental impact.